2015
DOI: 10.1117/1.oe.54.11.111308
|View full text |Cite
|
Sign up to set email alerts
|

Generalized phase contrast-enhanced diffractive coupling to light-driven microtools

Abstract: Abstract. We have previously demonstrated on-demand dynamic coupling to optically manipulated microtools coined as wave-guided optical waveguides using diffractive techniques on a "point and shoot" approach. These microtools are extended microstructures fabricated using two-photon photopolymerization and function as freefloating optically trapped waveguides. Dynamic coupling of focused light via these structures being moved in three-dimensional space is done holographically. However, calculating the necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…By designing a hollow microrobot that can be heated we introduced a syringe function for suctioning small particles from its immediate proximity and delivering the particles to a different location 21 . We have also reported wave-guided optical waveguides that have potential as single-cell tip-enhanced Raman scattering probes 44,45 . All these applications were made possible by the rational design of the microtools in relation to the target application.…”
Section: Microrobot Designs From Our Laboratorymentioning
confidence: 98%
“…By designing a hollow microrobot that can be heated we introduced a syringe function for suctioning small particles from its immediate proximity and delivering the particles to a different location 21 . We have also reported wave-guided optical waveguides that have potential as single-cell tip-enhanced Raman scattering probes 44,45 . All these applications were made possible by the rational design of the microtools in relation to the target application.…”
Section: Microrobot Designs From Our Laboratorymentioning
confidence: 98%
“…Our setup for catapulting microspheres benefits from an extended working distance made possible by using low numerical aperture (NA) objectives. [49][50][51] Using counter-propagating catapulting beams, it has also been demonstrated that such low NA setups can actuate microstructures by transversely translating and adjusting the relative intensities of the beam pairs. [49][50][51] Low NA objectives allow the light to interact with the sample environment in a wider, 3-D manner, which will allow us in the future to perform advanced studies using different microtools.…”
Section: Catapulting Particles With Generalized Phase Contrastmentioning
confidence: 99%
“…[49][50][51] Using counter-propagating catapulting beams, it has also been demonstrated that such low NA setups can actuate microstructures by transversely translating and adjusting the relative intensities of the beam pairs. [49][50][51] Low NA objectives allow the light to interact with the sample environment in a wider, 3-D manner, which will allow us in the future to perform advanced studies using different microtools. 45,48 Furthermore, this extended geometry facilitates the extraction of z-depth information through direct side-view imaging.…”
Section: Catapulting Particles With Generalized Phase Contrastmentioning
confidence: 99%
“…(5)-(10) show an opto-mechanical probe-interaction with a tiny surface-positioned object. Adapted from refs [3,4]…”
mentioning
confidence: 99%